PEMODELAN SEBARAN BOD DI SUNGAI KAPUAS KECIL BAGIAN HILIR MENGGUNAKAN WASP - Rizki Purnaini; Sudarmadji Sudarmadji; Suryo Purwono (Jurnal Teknosains, 2019)
The Kapuas Kecil River must be maintained for its water quality so that it can still be utilized in accordance with its designation. The purpose of this study is to predict water quality changes due to incoming waste from various sources of pollutants to the concentration of BOD in Kapuas Kecil River using WASP model as an effort to water quality monitoring and water pollution control.The study area to be simulated is Kapuas Kecil River passing through Pontianak City over ± 22 km from upstream to downstream (estuary) that divided into 42 segments. Water quality data were collected from several monitoring station locations in Kapuas Kecil River downstream, Landak River, effluent trenches located within the administrative area of Pontianak City, as well as secondary data on industrial effluents located along the study area. Water sampling method refers to the SNI 03-7026-2004, sampling was done once at each sample point with variations of the rainy and dry season, and at high and low tide conditions. Hydrometry data and river discharge can be obtained from primary and secondary data.The results showed that domestic and non-domestic of urban discharges that entering the river is very dominant influence on the water quality of the river. BOD concentration in rivers during the dry season is higher than rainy season both in high and low tide conditions. The simulation results of spatial distribution with all scenarios show that the accumulation of BOD pollution load begins after a distance of 5 km from the upstream boundary and then a significant increase in concentration occur at  segment 27 with loads originating from the Landak River and Pekong Trench. The BOD concentration then tends to fluctuate to a distance of 5 km before heading downstream, and after that it continues to decline towards the downstream.